2019
DOI: 10.1088/1367-2630/ab4927
|View full text |Cite
|
Sign up to set email alerts
|

Observation of orbital ordering and origin of the nematic order in FeSe

Abstract: In iron-based superconductors the interactions driving the nematic order that breaks the lattice fourfold rotational symmetry in the iron plane may also facilitate the Cooper pairing, but experimental determination of these interactions is challenging because the temperatures of the nematic order and the order of other electronic phases appear to match each other or to be close to each other. Here we performed field-dependent 77 Se-nuclear magnetic resonance (NMR) measurements on single crystals of iron-based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
(93 reference statements)
5
3
0
Order By: Relevance
“…We note that recent NMR experiments on FeSe find a dominant (≥80%) orbital contribution to the Knight shift at low temperature, in agreement with our model. 59,60 Also, the absence of any change in ΔK across the superconducting transition is consistent with an anisotropy arising from K orb and a very small K spin at low T (see Fig. 2a where our lowest data point at 1.5 K should be well below T c even for 15 T applied parallel to the planes 80 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We note that recent NMR experiments on FeSe find a dominant (≥80%) orbital contribution to the Knight shift at low temperature, in agreement with our model. 59,60 Also, the absence of any change in ΔK across the superconducting transition is consistent with an anisotropy arising from K orb and a very small K spin at low T (see Fig. 2a where our lowest data point at 1.5 K should be well below T c even for 15 T applied parallel to the planes 80 ).…”
Section: Discussionsupporting
confidence: 83%
“…Knight-shift anisotropy: experimental results When no stress is applied and the field is aligned with the Fe-Fe bonds (i.e., the orthorhombic a-or b-axis), NMR lines in the (nonmagnetic) orthorhombic phase are split into two peaks (Fig. 1a, c), in agreement with earlier studies of both LaFeAsO and FeSe 12,13,55,[59][60][61] . Upon applying uniaxial stress in both samples, the intensity of one peak grows at the expense of the other while the total intensity of the spectrum is conserved, as seen from Fig.…”
Section: Principle Of the Experimentssupporting
confidence: 89%
“…The spectra were measured at several temperatures down to 2.1 K using low-power rf pulses (π/2-pulse widths up to 80µs), sweeping frequency and summing the Fourier transforms. Our results are consistent with previous reports [15][16][17][18]27], and reveal a splitting of the single 77 Se resonance below T nem = 91 K due to twinning. The resonance frequencies are given by f = γH 0 (1 + K), where γ = 8.118 MHz/T is the gyromagnetic ratio and K is the Knight shift.…”
supporting
confidence: 93%
“…Recent NMR data found that anti-ferromagnetic spin fluctuations are present inside the nematic phase of FeSe 1−x S x , being strongest around x ∼ 0.1 [37]. In FeSe, spin fluctuations are rather anisotropic [37,38] and strongly field-dependent below 15 K [11]. Interestingly, the spin-fluctuations relaxation rate is enhanced below T * (Fig.…”
Section: Resultsmentioning
confidence: 94%